2015
DOI: 10.2147/nds.s74718
|View full text |Cite
|
Sign up to set email alerts
|

A review of gluten- and casein-free diets for treatment of autism: 2005–2015

Abstract: Background The gluten free, casein free (GFCF) diet is heralded by strong anecdotal parental reports to greatly improve and even “cure” symptoms of Autism Spectrum Disorders (ASD). Yet to date, little conclusive empirical evidence exists supporting its use. Objective The purpose of this paper is to provide an overview of the state of the recent evidence regarding use of GFCF diet for treatment of individuals with ASD. Methods Five database providers (PubMed, Web of Knowledge, EBSCO, ProQuest, and WorldCat)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 25 publications
0
31
0
2
Order By: Relevance
“…The opioid theory was the most cited theory for adopting of a CFGF diet for the treatment of ASD ( 67 , 68 ). It is known that, after digestion, certain types of peptides could cross the intestinal mucosa intact and may further cross the blood–brain barrier through bloodstream transportation and reach the central nervous system even to a high level in the case of impairments in intestinal track or celiac disease ( 69 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The opioid theory was the most cited theory for adopting of a CFGF diet for the treatment of ASD ( 67 , 68 ). It is known that, after digestion, certain types of peptides could cross the intestinal mucosa intact and may further cross the blood–brain barrier through bloodstream transportation and reach the central nervous system even to a high level in the case of impairments in intestinal track or celiac disease ( 69 ).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous reviews on this topic have been published, and they all concluded GFCF diet as lack of evidence for improving autistic symptoms ( 67 , 68 , 79 81 ). Overall, findings from current best evidence suggest that GFCF dietary may not help to reduce core symptoms of ASD neither gluten nor casein supplementation increase the symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Although, to our knowledge, this is the only study conducted to date, and further replication and extension of this study is required to elaborate on this finding, it has potential implications for people suffering from food allergies, because curcumin may influence allergenic responses to certain foods. Food allergies and sensitivities, particularly those associated with gluten, have been implicated in several diseases, including gastrointestinal disorders (103,104), rheumatic diseases (105), and even neurological and neuropsychiatric conditions such as depression (106), schizophrenia (107), autism (108,109), and dementia (110). However, the research is limited and often inconsistent.…”
Section: Antianaphylactic Effectsmentioning
confidence: 99%
“…There is increasing research into the effectiveness of the GFCF diet in children diagnosed with ASD. Several systematic reviews of GFCF diet studies in ASD have appeared [ 19 , 35 40 ]. However, the number of high quality RCTs is too small for drawing firm conclusions at this point and there are no meta-analyses available.…”
Section: Evidence For Elimination Diets’ Effects On Adhd and Asd Sympmentioning
confidence: 99%